Analisis Pengelolaan Fasilitas di Desa Wisata Taman Seribu Bunga Raya, Berastagi - Najwa Humairah (CV. Kurnia Grup, 2026)
This study aims to analyze the management of tourism facilities in the Taman Seribu Bunga Raya Tourism Village, Berastagi, using the POAC approach to examine primary facilities, supporting facilities, and auxiliary facilities according to Spillane’s theory. This study was motivated by the continued existence of several tourism facility issues, such as poorly maintained restrooms, damaged gazebos, restaurants that are no longer in operation, and suboptimal sanitation management. The research method employed was a descriptive qualitative approach using data collection techniques including observation, interviews, and documentation. The results of the study indicate that the management of tourism facilities has generally been quite effective, particularly regarding the flower garden as the main tourist attraction. However, there are still challenges in facility management, such as limited human resources, budget constraints, and suboptimal facility maintenance. Therefore, more targeted and sustainable facility management is required to enhance the quality of the tourism destination and improve visitor comfort in the Taman Seribu Bunga Raya Tourism Village.